Amphiphilic trismethylpyridylporphyrin-fullerene (C70) dyad: an efficient photosensitizer under hypoxia conditions. Issue 5 (10th December 2014) - Guan, Mirong; Qin, Tingxiao; Ge, Jiechao; Zhen, Mingming; Xu, Wei; Chen, Daiqin; Li, Shumu; Wang, Chunru; Su, Hongmei; Shu, Chunying
Abstract : Amphiphilic trismethylpyridylporphyrin-C70 (PC70 ) dyad with improved photosensitization has been successfully prepared. Abstract : Amphiphilic trismethylpyridylporphyrin-C70 (PC70 ) dyad with improved photosensitization has been successfully prepared. The PC70 dyad forms a liposomal nanostructure through molecular self-assembling. An increased absorption coefficient in the visible region, good biocompatibility, and high photostability were observed on the self-assembling structure. Surprisingly, in comparison with previously reported photosensitizer porphyrins, PC70 exhibited an enhanced photodynamic therapy (PDT) effect under hypoxia conditions. Further investigations illustrated that PC70 went through an extremely long-life triplet state (211.3 μs) under hypoxia, which enabled the exiguous oxygen to approach and interact with the activated ( 3 P-C70 )* more efficiently and produce more singlet oxygen. This would overcome the problem of existing photosensitizers of low PDT efficiency in cancerous tissues under hypoxia. The excellent properties of PC70 dyad make it a promising phototherapeutic agent, especially for the treatment of early- and late-stage cancers under shallow and hypoxia tissues.